Queer phenomenology: Orientations, objects, others - Ahmed, Sara (Duke University Press, 2006)
"In this groundbreaking work, Sara Ahmed demonstrates how queer studies can put phenomenology to productive use. Focusing on the “orientation” aspect of “sexual orientation” and the “orient” in “orientalism,” Ahmed examines what it means for bodies to be situated in space and time. Bodies take shape as they move through the world directing themselves toward or away from objects and others. Being “orientated” means feeling at home, knowing where one stands, or having certain objects within reach. Orientations affect what is proximate to the body or what can be reached. A queer phenomenology, Ahmed contends, reveals how social relations are arranged spatially, how queerness disrupts and reorders these relations by not following the accepted paths, and how a politics of disorientation puts other objects within reach, those that might, at first glance, seem awry. Ahmed proposes that a queer phenomenology might investigate not only how the concept of orientation is informed by phenomenology but also the orientation of phenomenology itself. Thus she reflects on the significance of the objects that appear—and those that do not—as signs of orientation in classic phenomenological texts such as Husserl’s Ideas. In developing a queer model of orientations, she combines readings of phenomenological texts—by Husserl, Heidegger, Merleau-Ponty, and Fanon—with insights drawn from queer studies, feminist theory, critical race theory, Marxism, and psychoanalysis. Queer Phenomenology points queer theory in bold new directions." -- Tiré du site de l'éditeur
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; corps; cours; discipline; fem1000; féminisme décolonial; identité sexuelle; identités LGBTQIA2+; incontournable; lit4700; militance; occident; orient; philosophie; phénoménologie; premier cycle; périodes historiques; queer; queer of color; rapports de domination; rapports sociaux de sexe; sciences humaines; sex3383; thématiques; violences; études culturelles

Routledge international encyclopedia of queer culture - Gerstner, David A. (Routledge, 2006)
The Routledge International Encyclopedia of Queer Culture covers gay, lesbian, bisexual, transgender and queer (GLBTQ) life and culture post-1945, with a strong international approach to the subject.The scope of the work is extremely comprehensive, with entries falling into the broad categories of Dance, Education, Film, Health, Homophobia, the Internet, Literature, Music, Performance, and Politics. Slang is also covered. The international contributors come from a wide array of backgrounds: scholars, journalists, artists, doctors, scientists, lawyers, activists, and an enormous range of ideologies and points of view are represented. Major entries provide in-depth information and consider the intellectual and cultural implications of their subjects in a global context. Information is completely up-to-date, including full coverage and analysis of such current or ongoing issues as same-sex marriage/civil union and the international AIDS epidemic. Additionally, there are important appendices covering international sodomy laws and archival institutions, which will be of great value to researchers. The Encyclopedia is fully cross-referenced and many entries carry a bibliography. Where possible internet references have been given and there is a full index.The combination of its wide scope, determined international coverage and appendices make the Routledge International Encyclopedia of Queer Culture a uniquely ambitious work and an extremely rich source of information. It is a priority addition for all libraries serving scholars and students with an interest in GLBTQ culture, history and politics across the disciplines.
Keywords: LGBTQIA2+; approches et analyses; identités LGBTQIA2+; incontournable; outils; ouvrages de références; queer; ressource en ligne; thématiques